Treatment of an Adult Patient with Skeletal Class II and Unilateral Cross-bite - Seher Gündüz-Arslan; Jalen Devecioğlu-Kama; Atılım Akkurt (Galenos Yayinevi, 2007)
The purpose of this case report is to represent the treatment of adult sketetal Class II malocclusion with posterior cross-bite. Our patient was 24.2 years old a female. According to intraoral observation, a maxillary protrusion and posterior cross-bite were determined with Angle Class I motar relationship. Due to the cephalometric analysis, ANB and SNGoGn angles were 7° and 50° respectively. And also she had a Bolton discrepancy of 6 mm. The patient refused orthognathic surgery procedure, so her orthodontic problem was decided to achieve orthodontically without surgery. For elimination of posterior cross-bite rapid maxillary expansion (RME) appliance was used, however maxillary expansion could not accomplished. Thus, a quad-helix was used for maxillary expansion with an occlusal bite plane on the upper left molars side to prevent the expansion on this side. After expansion, fixed orthodontic appliances were applied with an occipital headgear. The cooperation of our patient was quite well. She has been wearing the extraoral appliances more than asked. Because of this a baldness which called traumatic areata were occurred on her occipital scalp region. Bolton discrepancy was compensated with a little amount of diastema behind the upper canines. Finally; maxillary protrusion and posterior cross-bite were treated with 3,5° reduction of vertical dimension. At the end of the treatment, an acceptable occlusion and facial esthetic were obtained